Construction of half-sandwich rhodium- and iridium-based metallamacrocycles with different space conformations via isomeric pyridyl-substituted ligands. Issue 11 (3rd July 2018) - Deng, Yu-Xin; Zhang, Hai-Ning; Lin, Yue-Jian; Jin, Guo-Xin
Abstract: Herein, we describe the utilization of isomeric pyridyl-substituted ligands featuring different coordination vectors to rationally design and construct a series of discrete organometallic assemblies with specific space conformations. In the case of tetranuclear macrocycles constructed from the ligand3-bpb, different conformations of these assemblies with C 2v and C 2 h point symmetry were revealed by single-crystal X-ray diffraction. These complexes were further characterized by X-ray crystallography, 1 H NMR, DOSY NMR, IR spectroscopy, and elemental analyses. Abstract :